The Role of Islamic Social Finance in Mitigating Humanitarian Crises: A Multi-Range Strategy to Mitigate COVID-19 Impacts - Hamed, Mustafa Mahmoud (European Journal of Islamic Finance, 2020)
The economic shutdown resulting from the COVID-19 pandemic across countries has caused huge impacts on various industries which are cutting down production and jobs. This led to many socio-economic risks, such as high unemployment rates, low income rates, increasing risks of poverty and hunger. This study explores the validity of the proposition that the Islamic social finance have an effective role in mitigating the humanitarian crises risks. So the paper tries to provide a multi-range strategy for maximize the benefit from Islamic social financing tools such as zakat, sadaqah, and waqf in short, medium and long range, and choosing the well-suited tool in each range of the strategy, in order to effective handling the social impacts of COVID-19. This paper reviews the conceptual definitions of Islamic social finance, and its various instruments. The study relied primarily on sources gathered from ongoing researches, news articles, reports, and information recorded by verified online sources of information. The results indicate that the multi-range strategy of Islamic social finance providing an innovative way which can helps governments and policy makers for manage the crisis during and after the COVID-19 pandemic. Keywords; humanitarian crises; COVID-19 impacts; Islamic social finance; Islamic social finance tools